EVALUATION OF THE IMPLEMENTATION OF SIMULATION-BASED LEARNING IN FOURTH YEAR MEDICAL STUDENTS OF ATMA JAYA CATHOLIC UNIVERSITY OF INDONESIA - Rhevensa Santoso; Natalia Puspadewi; Tommy Tanumiharja (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2018)
Background: Health care providers must achieve and maintainthe required competencyin providing services to patients; even more so in complex and stressful situations. Medical simulation is a method to facilitate training and assessment of clinical skills in medical students and physicians. This method has been implemented and recognized in many areas outside medicine, but because of various problems this method is relatively difficult to apply in the field of medicine.Methods: The design of this study was cross-sectional with quantitative method. Study participants were the fourth year students of Atma Jaya Catholic University of Indonesia, School of Medicine. Simulation-based learning (SBL) was implemented by a 2-day workshop. Participants were given a pretest and posttest to assess the cognitive aspect of their clinical skills, and assessment of case simulation using Objective Structured Clinical Examination (OSCE) and Team Observed Structured Clinical Examination(TOSCE) for their clinical and soft skills.Results: The difference of the knowledge before and after the intervention was not significant(p = 0,071). However, there was a significant difference of the clinical skills (p < 0,001) and soft skills (p < 0,001).Conclusion: Using SBL as a learning method can increase clinical skills and soft skills of the students significantly. To a smaller extent, using simulation based learning as learning method can increase knowledge of the students about SBL and cognitive aspect of clinical skills although itis statistically insignificant.